Interactions of phospholipids with the potassium channel KcsA. - Williamson, Ian M (2002)
The potassium channel KcsA from Streptomyces lividans has been reconstituted into bilayers of phosphatidylcholines and fluorescence spectroscopy has been used to characterize the response of KcsA to changes in bilayer thickness. The Trp residues in KcsA form two bands, one on each side of the membrane. Trp fluorescence emission spectra and the proportion of the Trp fluorescence intensity quenchable by I(-) hardly vary in the lipid chain length range C10 to C24, suggesting efficient hydrophobic matching between KcsA and the lipid bilayer over this range. Measurements of fluorescence quenching for KcsA reconstituted into mixtures of brominated and nonbrominated phospholipids have been analyzed to give binding constants of lipids for KcsA, relative to that for dioleoylphosphatidylcholine (di(C18:1)PC). Relative lipid binding constants increase by only a factor of three with increasing chain length from C10 to C22 with a decrease from C22 to C24. Strongest binding to di(C22:1)PC corresponds to a state in which the side chains of the lipid-exposed Trp residues are likely to be located within the hydrocarbon core of the lipid bilayer. It is suggested that matching of KcsA to thinner bilayers than di(C24:1)PC is achieved by tilting of the transmembrane alpha-helices in KcsA. Measurements of fluorescence quenching of KcsA in bilayers of brominated phospholipids as a function of phospholipid chain length suggest that in the chain length range C14 to C18 the Trp residues move further away from the center of the lipid bilayer with increasing chain length, which can be partly explained by a decrease in helix tilt angle with increasing bilayer thickness. In the chain length range C18 to C24 it is suggested that the Trp residues become more buried within the hydrocarbon core of the bilayer.